Volatility spillovers and time varying correlation for Chinese tourism firms - Gokmenoglu, Korhan K.; Al Al Hadood, Abobaker (Routledge Journals, Taylor & Francis Ltd, 2019)
This paper analyses the volatility spillover between foreign exchange rate and tourism firm stock returns for the case of China 4 July 2011 to 27 September 2018 period which covers the post-transition of Chinese managed floating exchange rate regime. Utilizing the BEKK-GARCH model, the empirical results indicate that there is bidirectional long-term spillover volatility between the variables under investigation. Our findings provide a new insight to portfolio managers about how the volatility is transferred between foreign exchange rate and tourism firm stock returns, and to which extent they are correlated over time. These elements are essential for portfolio diversification.
Keywords: Volatility spillover; time-varying correlation; foreign exchange rate transitions; firm stock prices; tourism industry; Asia Pacific; China; BEKK-GARCH model; portfolio diversification; traders strategy